The basketball pass: A systematic review - Quilez Maimon, A.; Courel-Ibanez, J.; Rojas Ruiz, F. J. (Journal of Human Kinetics, 2020)
The aim of this study was to review and organise current literature about the basketball pass and find the main factors that influence its learning skills and performance. Thirty-seven studies were included after the screening process. The documents were classified into main research topics. This review identified the following conclusions: (i) the assessment of passing performance should be made under uncertain and variable conditions to obtain information on players` responses to competitive scenarios, (ii) it is advisable to incorporate new and random activities to facilitate the transference of learning to the competition, (iii) it is recommended to include overwhelming factors during the practice to minimise the effect of pressure and choking, (iv) optimal physical conditioning is essential to maintain passing performance during a basketball game, (v) small sided games and changing environments stand as the best training situations to improve passing skills. Furthermore, limited information is available about biomechanical aspects and physical conditioning training programs to improve passing skills in basketball. Likewise, there is sparse data on passing skills development in children.